Discourses of Fear in Online News Media: Implications for Perceived Risk of Travel - Kelley A. McClinchey; Frederic Dimanche (Tourism and Hospitality, 2023)
This paper analyzes the role of Canadian online news media in framing travel during the pandemic. The article applies Altheide’s concept of the problem frame to reflect how news media contribute to the emergence of a highly rationalized problem that, in turn, generates a discourse of fear. While the impacts of COVID-19 on tourism have been extensively examined within tourism scholarship, less attention has been devoted to the impact of news media. Because travel and the pandemic are heavily intertwined, discourse analysis can help process media narratives, furthering our understanding of their role in influencing perceived risk of travel. A critical discourse analysis of over 100 online news articles was conducted using thematic analysis to uncover themes in Canadian media sources and to explore how the media have framed travel during the pandemic. The role of online news media in promoting fear was communicated through the themes of anxiety, antitrust, avoidance, and animosity. The role of the media in producing the problem frame in the context of travel was examined as well as its implications for perceived travel risk and tourism demand. The power dynamics between media, government, and the citizens it serves are also discussed.